Experimental modeling of a square planar micro-coil - Assia Ouali; Fatima Zohra Medjaoui; Azzedine Hamid; Mohamed Rizouga; Abderahim Mokhefi; Hocine Guentri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
This study focuses on developing miniaturized electromagnetic components for applications in integrated microsystems, magnetic sensors, contactless energy transfer, and compact power converters. In a context of miniaturization and the pursuit of greater energy efficiency, the planar micro-coil plays a key role due to its compact size, ease of integration, and compatibility with microfabrication technologies. The work presented explores the design, modeling, fabrication, and experimental characterization of a square planar micro-coil. Its electromagnetic properties, such as inductance, resistance, and quality factor, are highly dependent on factors like the coil’s geometry (turns, track width, spacing, conductor thickness), substrate characteristics, and the manufacturing process. The main goal is to propose an accurate experimental model linking geometric parameters to electrical performance. The approach combines analytical modeling, finite element modeling (FEM), and experimental measurements on microfabricated prototypes. The results show strong agreement between theoretical predictions and experimental data, validating the model’s relevance. Lastly, the study highlights the impact of skin effects, proximity effects, and ohmic losses on the coil’s performance, offering insights for optimizing its design for high-performance, compact electromagnetic devices.